Almond selection in microclimate areas of northeast Anatolia - Aslantas R.; Güleryüz M. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
Northeast Anatolia is the highest altitude region of Turkey. There are high mountains and wide valleys in which fruit grown is naturally. Upper Firat river basin and Çoruh valley are the most important micro climate areas in the region. Seventeen almond types having late flowering properties were selected in the region during 1992 and 1997. Flowering time and period of the almond types started between 5 April and 3 May and between 8 and 10 days, respectively. The almond types had 3.02-6.14 g at average in-shell weight, 0.72-1.15 g at kernel weight, 14.66-26.81 per cent at kernel rate, 0.0-20.0 per cent at double kernel rate, and 96.0-100.0 per cent at sound kernel rate. These selected almond types were budded in collection parcel at the Horticultural Research Institute of Erzincan in 1997.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)